PONDASI TIANG PANCANG DAKTAIL - Indrastono Dwi Atmanto (Diponegoro University, 2013)
The driven ductile iron pile is a simple and economical driven foundation system made from ductile iron pipes.The pipe material is centrifugally-cast ductile iron, which has excellent ductility, strength, and corrosionresistance properties. The material behavior and the manufacturing of the pipes in the plant are described.Questions concerning corrosion are treated. The internal and external bearing capacity is discussed as well asthe production of the piles on construction sites. Finally the range of application in practice is presented.